Elaboración de una cartilla didáctica de conceptualización tributaria básica para los emprendedores de Villavicencio Meta (2021)
Tax conceptualization includes knowledge of the regulations of a tax system. Entrepreneurs who are creators of viable productive projects and generators of wealth are immersed within the tax system. In Colombia, tax regulations are extensive and have few information disclosure mechanisms in a didactic and understandable way, therefore it is important to strengthen the entrepreneur's tax conceptualization. In the case of the municipality of Villavicencio Meta, the entities in charge of helping the entrepreneur focus on the formalization of their businesses, neglecting the strengthening of knowledge in tax matters. The purpose is to prepare a booklet that contains the tax conceptualization concerning the entrepreneur from Villavicencio that strengthens their knowledge of the regulations that govern the country. It is intended to provide knowledge from the accounting profession to the entrepreneur so that he can achieve the good development of his tax life. In the development of the work, the specific competences in tax matters developed by the entrepreneur are identified with the booklet and the thematic structure of basic tax conceptualization for entrepreneurs.